SPERM MEDIATED GENE TRANSFER IN LABEO ROHITA (HAMILTON 1822) - SHEELA, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
'Transgenesis' may be defined as the introduction of exogenous DNA by different methods such as microinjection, sperm mediation electroporation etc. into the host genome resulting in its stable integration, expression and transmission. In the present study sperm-mediated gene transfer was carried out in ROHU (Labeo rohita) using melanin concentrating hormone gene, (p-CMV-MCH). Milt was soaked in different concentrations of plasmid DNA (50-200 µg / ml) for 10 minutes and it was used to fertilize the eggs. Slot blot analysis was carried out to study the integration of transgene. It showed integration of foreign genes which indicates that the carp sperm do pick up DNA in about 10 minutes. Moreover the MCH gene causes contraction of melanophores in the body, caudal region and on the eyeball resulting in brightness of the transgenic fish. Therefore this study clearly indicates that MCH gene construct can be used as a marker gene to identify transgenesis and to study the molecular basis of gene integration expression and transmission.